Análisis de la gestión financiera y su incidencia en la planeación estratégica de la Ferretería Manantial Guihon SAC año 2016 - Leon Saldaña, Alcira Mirella (2016)
The purpose of this research was to investigate whether, with the Financial Management Analysis, the degree of impact in the strategic planning of the GUIHON SAC Spring Hardware 2016 "of the district of Pacasmayo. Every company, to operate normally and grow necessarily and must seek sources of financing, that allows to acquire the means necessary to obtain the liquidity and the planned profitability, for it must make use of the own tools of the Techniques of Financial Analysis and Economice to measure Its real situation of payment and productivity. The present research work has been developed with the above procedure; The data were obtained and surveys and interviews were applied, in this specific case of the Manantial Hardware GUIHON SAC in the years 2015 and 2016; Which allowed us to reach the final conclusions, applying techniques of analysis and interpretation of Financial Statements, it was possible to achieve as a result of research a better strategic planning for a better financial management of the Hardware Manantial GUIHON SAC. According to page 80 of Chapter III Result was concluded and recommended on the business situation of the Manantial Hardware GUIHON SAC. the next: 1. Liquidity Ratios: Improve cash increase. 2. Management Ratios: Improve inventory rotation. 3. Solvency Ratios: Improve the capital structure. 4. Profitability Ratios: Improve return on assets, assets and sales. And the following Action Plan was proposed in favor of the Manantial Hardware GUIHON SAC (page N ° 81 of results). Consequently it was possible to fulfill the objective of the research and with the knowledge obtained to support the company subject of study,